A Mixed Variant of Castleman Disease Detected by Somatostatin Receptor Scintigraphy with 99mTc-HYNIC-TOC and 18F-FDG PET/CT. (February 2019) - Pan, Qingqing; Zhang, Xin; Luo, Yaping; Ma, Yanru; Li, Fang
Abstract : Abstract: A 50-year-old woman was found with a hypervascular abdominal mass in the right lower quadrant in contrast-enhanced CT. Somatostatin receptor scintigraphy with 99m Tc-HYNIC-TOC showed positivity of the abdominal mass and detected additional lesion with moderate increased radioactivity in the right axilla. In 18 F-FDG PET/CT, both of the lesions were FDG-avid. A hypermetabolic node in the right supraclavicular fossa was also noted. The histopathological examination of the abdominal mass after surgical resection revealed Castleman disease, a mixed hyaline vascular and plasma cell variant. The right axillary and supraclavicular lesions were considered involvement of Castleman disease.